2001
DOI: 10.1007/s002960100119
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Notch homologues in the synovium of rheumatoid arthritis and osteoarthritis patients

Abstract: Notch is known as a receptor that controls differentiation or proliferation in various cells and is associated with several diseases. The objective of the present study was to clarify whether human Notch homologues Notch-1, -2, -3, and -4 are expressed in synovium and synoviocytes from rheumatoid arthritis (RA) and osteoarthritis (OA) patients. Immunohistochemical staining showed that Notch-1, -2, and -3 were clearly expressed in the synovium from both RA and OA, whereas Notch-4 was only slightly detected. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…This diversity may be due to the different stimulation concentration of TNF- α used in experimental system or the different culture times. Indeed, the expression profile of Notch receptors or ligands in RA local synovium tissue also varied among previous reports [7, 8, 11]. Nevertheless, here we confirmed the result that TNF- α could induce the activation of Notch signaling in cultured RA FLSs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This diversity may be due to the different stimulation concentration of TNF- α used in experimental system or the different culture times. Indeed, the expression profile of Notch receptors or ligands in RA local synovium tissue also varied among previous reports [7, 8, 11]. Nevertheless, here we confirmed the result that TNF- α could induce the activation of Notch signaling in cultured RA FLSs.…”
Section: Discussionsupporting
confidence: 88%
“…Ishii et al and Yabe et al showed that the expression pattern of Notch homologues among synovium from OA and RA patients differed from that of normal subjects [7, 8]. Another report demonstrated the expression of Notch-1 in synoviocytes and the presence of Notch-1 fragment in the nuclei of RA synoviocytes and suggested the involvement of Notch-1 signaling in the TNF- α -induced proliferation of RA synoviocytes [9].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that there is a high level of expression of DLL-1, Jagged-1, Notch-1, Notch-2 and Notch-3 in the synovium of RA patients 9 41. However, the precise role of each Notch ligand in autoimmune diseases remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, blockade of Dll1, as well as Jagged1, did not affect the parameters of bone strength and structure in the absence of any stimulation as shown in sham-operated mice. A high expression of Dll1 and Jagged1 as well as Notch1, Notch2 and Notch3 has been demonstrated in the synovium of RA patients [30,31]. We previously demonstrated that Dll1 was expressed on a part of the macrophage population and that inflammatory cytokines, such as tumor nuclear factor-alpha or interferon-gamma, induced the expression of Dll1 on macrophages [9].…”
Section: Discussionmentioning
confidence: 99%